Gangguan Skizofrenia pada Tokoh Utama dalam Novel Skizofrenia Karya Disadisso : Kajian Psikologi Sastra Lev Vygotsky - Sheila Rohmatika Fitria; Ahmad Ilzamul Hikam (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Mental disorders, particularly schizophrenia, are psychological phenomena that are widely addressed in literary works because they can reflect the inner conflicts of individuals as well as the social problems surrounding them. This study aims to uncover how schizophrenia is represented in the main character of the novel "Skizofrenia" by Disadisso using a psychological literary approach based on Lev Vygotsky's sociocultural theory. The method used is descriptive qualitative, with data collection techniques involving reading and noting the text of the novel. Data are analyzed through the grouping of schizophrenia symptoms, tracing causes, and examining the influence of social interactions on the character's development of the disorder. The results show that the main character, Fara, experiences various symptoms of schizophrenia such as hallucinations, delusions, social withdrawal, and thought disorders, which arise from psychosocial stress, childhood trauma, and a lack of social and family support. The conclusion of the study This research emphasizes that schizophrenia is not only a mental disorder from a purely medical perspective, but also a result of the failure of social and repressive cultural relationships, which is clarified through the literary psychology approach of Lev Vygotsky.